English Used by Sri Lankans on Social Media: A Discourse Analysis Based on Contemporary Facebook Content - Gamage, G.D.U.P.K.; Maheshwaralingam, G.; Vithanage, A.V.D.K.N.; Senaweera, S.A.T.P. (University of Jaffna, 2025)
English being a link language in Sri Lanka, a multicultural country, plays a significant role in sharing opinions on social media. A rapid increase in the use of Facebook could be observed following the outbreak of the COVID-19 pandemic. It was also observed that a considerable number of Facebook users in Sri Lanka, approximately 40% of its population, use Facebook for diverse reasons. The main objective of the study is to explore unique morphological, syntactic, semantic, and pragmatic features of English used by Sri Lankans, which are shaped by extralinguistic factors such as socioeconomic, cultural, psychological, and political influences. In order to accomplish the aforesaid objective, 200 Facebook posts, including comments and replies made by academics, politicians, celebrities, differently-abled people, and typical Facebook users, were analyzed. A qualitative approach was adopted to align with the objectives of the study. During the data collection process, Facebook posts and comments in English shared by Sri Lankan Facebook users were selected using the purposive sampling technique. Discourse analysis was employed to analyze the data under four themes: morphology, syntax, semantics, and pragmatics. The overall findings and analysis of the study revealed several key features across different linguistic categories. Morphological features explored include abbreviations, reduplications, compounding, clitics, transliteration, and mother tongue influence. Syntactic features involve changes in word order and sentence patterns, subject- verb agreement, negation, voice, ellipsis, coordination, subordination, sentence fragments, interrogation, punctuation, neglect of capitalization rules, and reduced expressions. Semantic features encompass connotation and denotation, cohesion, presupposition, and the influence of the mother tongue. Finally, pragmatic features highlight a range of speech acts, such as emphases, formal and informal expressions, sarcastic remarks, and translanguaging. The research concludes that the English language used by Sri Lankans in Facebook posts, comments and replies encompasses unique linguistic features, influenced by socioeconomic, cultural, psychological, and political factors.
Keywords: Facebook content; Linguistic features; Sri Lankan English; Extralinguistic factors